Optimization of critical land empowerment through coffee plant extensification as an effort to improve the economic level of coffee farmers in Indonesia - Eri Yusnita Arvianti; Ratna Wati; Cakti Indra Gunawan; Karunia Setyowati (Brawijaya University, 2023)
Critical land in Indonesia is the result of weather disturbances, natural disasters, farming behavior without considering the preservation of nature, and the unwise use of chemical fertilizers. Critical land tends to be acidic and has a soil structure that does not support cultivation. Coffee plants are flexible plants, and their root systems and ecology can improve soil structure. The need for coffee at home and abroad tends to increase along with the development of coffee consumption as a lifestyle for Generation Z (Gen-Z). The economic value of coffee, which tends to increase, opens the insight of farmers to continue to develop this coffee plantation area. In the development of planting areas, knowledge of critical land optimization is needed, which is a principal factor as the basis for implementing critical land extensification. For this reason, the purpose of this study was to determine the level of knowledge of farmers on optimizing critical land into strategic land and efforts to develop coffee agribusiness in critical land. This study used a quantitative descriptive method and used the SmartPLS3 analysis tool. The results showed that internal factors, external factors, and motivation of farmers affect the level of knowledge about optimization of critical land, critical land management must meet ecological conservation and improve the community's economy in a structured manner, the extensification of critical land using coffee plants is one of the strategic steps for critical land optimization, as well as the development of coffee agribusiness, both seeds and waste as an effort to increase farmers' income.